Analysis Of Cohesion In Disney English Comics Rapunzel - Adelia Prabawati, Faktian, Drs. Sigit Haryanto,M. Hum (2017)
The research aims at describing the grammatical and lexical cohesion of Disney English Comics Rapunzel. The object of the research is Disney English Comics Rapunzel. The data are those sentences containing grammatical and lexical cohesion found in Disney English Comics Rapunzel. In collecting the data, the researcher chooses documentation techniques consisting of reading Disney English Comics Rapunzel and discourse analysis books, identifying the grammatical and lexical cohesion by making some notes on the discourse, and writing the words, phrases, and sentences on the data sheets to be used in the data analysis. In analyzing the data, the researcher describes words, phrases, and sentences based on their grammatical and lexical cohesion. Finally, the researcher classifies them based on the description and theories of discourse analysis. After analyzing the data, the researcher finds both grammatical and lexical cohesion. Grammatical cohesion consists of 14 personal references, 9 demonstrative references, 1 comparative reference, 1 substitution, 1 ellipsis, 4 additive conjunctions, 1 comparative relation conjunction, 1 appositive relation conjunction, 6 adversative conjunctions, 5 causal conjunctions, and 1 temporal conjunction. Lexical cohesion consists of 5 repetitions, 2 near synonyms, 3 partial synonyms, 1 absolute synonym, 2 relation oppositions, 1 absolute opposition, and 2 collocations. Key words: Grammatical cohesion, lexical cohesion